Anticolonialism as a Guiding Principle of Chinese Foreign Policy - I. Y. Zuenko; Cui Heng (Международная аналитика, 2023)
This article explores the ideology of anticolonialism as a guiding principle in the foreign policy of the People’s Republic of China (PRC). It highlights the close association of anticolonialism with decolonialism, anti-imperialism, and the Nonaligned Movement, emphasizing their importance throughout the history of the PRC. While the current Chinese leadership may not emphasize anticolonial rhetoric as frequently as during the Mao Zedong era (1950–1970s), the core essence of Chinese foreign policy remains unchanged. China acknowledges its former semi-colonial status and aligns its policies with the interests of developing countries, seeking cooperation to protect its own interests amidst potential superpower pressures. Recent initiatives by Xi Jinping, such as the Belt and Road Initiative and the concept of a “Community with a shared future for mankind,” demonstrate a universal character that extends beyond developing countries. Authored by scholars from Russia and China, this article aims to familiarize the international audience with China’s oﬃcial discourse on its semi-colonial past, anticolonialism, and decolonization. The authors also highlight the potential for cooperation between Russia and China based on their shared perspectives on these issues. Understanding China’s foreign policy principles provides valuable insights into its historical context and contemporary approach to international relations.